Analisis Perbandingan Kinerja Keuangan Bank Pemerintah dan Bank Swasta di Bursa Efek Indonesia (BEI) Periode 2008 – 2012 - Vivi Putri Maharani; Chairil Afandy (Management Insight: Jurnal Ilmiah Manajemen, 2014)
The purpose of this research was to determine whether there are significant differences in the (LDR, NPL, ROA, ROE, ROA, NIM and PDN) between government bank compared to private banks in Indonesia Stock Exchange (IDX) the period of 2008-2012. Method of sample selection was done by purposive sampling, the samples obtained from government banks  such as BNI, BRI, BTN, and Mandiri bank, while from private banks such as BCA, BII, CIMB Niaga Bank and Panin Bank. Data analysis methods is hypothesis testing using two different test mean (pair sample t test). The results showed that the financial performance of the ratio for LDR, NPL, ROA, ROE, ROA and PDN there is no significant difference between the government banks and private banks. While the financial performance of the NIM ratio there are significant differences between the government banks and private banks.